Seismic performance of steel corrugated plate structural walls with different corrugation inclinations. (May 2022) - Zheng, Liang; Wang, Wen; Ge, Hongwei; Guo, Hong; Gao, Ying; Han, Yunshan
Abstract: The placement angle, height, and spacing of the corrugation have a significant influence on the seismic performance of steel corrugated plate shear walls. In this study, steel corrugated plate shear wall structures with corrugation angles of 0°, 30°, 45°, 60°, and 90° were designed. The corrugation spacing and height were 600 and 100 mm, 600 and 200 mm, and 800 and 100 mm, respectively. In total, 15 models of steel corrugated plate shear wall structures were established using the finite element software. Under cyclic loading, the analysis included the hysteretic curve, degradation in bearing capacity, energy dissipation coefficient, failure mode, out-of-plane deformation of the wall, fracture trend of the steel plate, and change in bearing capacity under initial loading in the hysteretic curve of steel corrugated plate shear walls with different parameters. The analysis showed that the seismic performance of the shear wall is the best when the corrugation is placed at an angle of 90°. The height of the corrugation has a significant influence on the seismic performance of the shear wall, while the spacing of the corrugation has little influence on it. When the corrugation is placed obliquely, the steel corrugated plate shear wall exhibits different seismic performances under tension and compression. The hysteretic curve of the shear wall under tension is fuller than that under compression, and the bearing capacity of the steel corrugated plate shear wall under tension is higher than that under compression. Highlights: Seismic performance of steel corrugated plate shear wall under different corrugation inclinations was studied. The optimal placement angle of corrugation is proposed. Energy dissipation capacity, degradation property, stiffness, failure mode, and deformation modes under low-cyclic loading were studied.